Prediction of the normal contact stiffness between elastic rough surfaces in lubricated contact via an equivalent thin layer. (26th February 2020) - Sun, Yunyun; Chuang, Ho-Chiao; Xiao, Huifang; Xu, Jinwu
In this work, the normal contact stiffness of lubricated rough interface is evaluated theoretically by describing the lubricated rough interface as an equivalent thin layer. Layer parameters, including equivalent thickness and effective Young's modulus, are used to characterize the normal contact stiffness by incorporating the contributions of asperity contact and lubricant contact simultaneously. On the basis of layer parameters, the normal contact stiffness of lubricated rough interface is obtained as a function of interfacial separation, surface topography, and properties of contacting solids and lubricants. Effects of surface topographies and lubricant types on the normal contact stiffness are investigated at varying interfacial separations and contact area fractions. The proportion of solid stiffness and lubricant stiffness from the total normal stiffness is also discussed. Numerical solutions reveal that the normal contact stiffness depends sensitively on the lubricant property at initial contact, whereas the influences of surface topographies become obvious with the decrement of interfacial separation or increment of contact area fraction. Comparisons between the predicted values of normal contact stiffness and experimental data for both dry interface and lubricated interface are presented to validate the rationality of the developed model.